“HE WHO LIVES IN A GLASS HOUSE SHOULD NOT THROW STONES”: NIKITA KHRUSHCHEV’S PROVERBIAL SPEECHES AT THE UNITED NATIONS - Carter, Elena V. (Proverbium - Yearbook, 2015)
Premier Nikita Khrushchev’s two visits to the Unites States in 1959 – 1960 were a historical event due to the fact that it was the first time that the Soviet leader arrived in America. People from all over the world focused on his personality as well as his behavior and manner of speaking. Khrushchev’s fondness for the simple peasant phrase was one of his most striking features that was frequently demonstrated in unofficial talks as well as in different formal settings. Considering the fact that little is known about the use of pithy folk sayings by the Russian politician at the United Nations, the paper aims to examine Khrushchev’s proverbial rhetoric in this official environment.